Heat current method for analysis and optimization of heat recovery-based power generation systems. (15th December 2019) - Chen, Xi; Chen, Qun; Chen, Hong; Xu, Ying-Gen; Zhao, Tian; Hu, Kang; He, Ke-Lun
Abstract: Performance improvement of heat recovery-based power generation (HRPG) systems puzzles researchers due to the implicitly coupled property. This contribution builds the heat current model of a HRPG system and applies the circuit principle to derive its heat transfer and conversion constraints. Then, derivation of the flow resistance balance equations describes the pressure distribution in circulation loop. Combining with the relations between fluid temperatures and pressures constructs the integrated system model. Based on the separation of linear topology equations and explicit nonlinear component equations from implicit nonlinear constraints using heat current model, this contribution introduces a fast and stable divide-and-conquer solution scheme, which solves linear equations in iterations and updates the iterative variables by substitutions. Finally, optimization of the fluid flow rates for the maximum net electricity generation under different working conditions shows the superiority of the heat current method over the commercial software Ebsilon. The optimized results show that a smaller mass flow rate of flue gas leads to lower optimal evaporation and condensation pressures, while the optimal dryness fraction of exhaust steam is almost unchanged. Besides, the constant backpressure operation strategy apparently deviates from the optima, and the maximum deviation reaches 8.6%. Highlights: Develop a standardized model construction strategy for HRPG systems. Build a heat current model to reflect the global heat transfer and conversion laws. Propose a more stable solution scheme with minimal nonlinear implicit equations. The optimal dryness fraction of exhaust steam is almost unaffected by flue gas. Constant backpressure operation mode apparently deviates from the optimums.